Evaluating the Effect of Different Sand Types on the Physical, Mechanical, and Durability Properties of Sandcrete Blocks in Ghana - Wahab Adamu; Acquah Edward; Appiah-Kubi Emmanuel; Alfred Osei (Journal of Building Materials and Structures)
The type of sand used in the production of sandcrete blocks greatly influences their strength and durability, which are essential building material qualities in Ghana's construction industry. This study examines how the structural integrity of sandcrete blocks is affected by three different types of sand: pit, river, and sea sand. The mechanical, chemical, and physical characteristics of locally sourced materials were examined in accordance with ASTM guidelines. To create 126 specimens for the experiment, a mixed design with a 1:6, cement-to-fine aggregate ratio and a constant water-to-cement ratio of 0.5 was employed. According to the results, pit sand blocks were the best option for load-bearing structures because they had the highest compressive strength (8.56 N/mm²) and tensile strength (1.69 N/mm²), the lowest abrasion resistance (0.62%), and the water absorption rate (8.02%). On the other hand, blocks made of river sand performed moderately well, exhibiting abrasion resistance of 1.46%, tensile strength of 0.92 N/mm2, and compressive strength of 3.26 N/mm². However, questions about long-term durability are raised by their higher water absorption rate (13.11%). Sea sand-based blocks were the weakest, with a compressive strength of 2.87 N/mm2, a tensile strength of 0.87 N/mm2, abrasion resistance of 1.97%, and the highest water absorption rate (13.42%),  The main cause of this weakness is the high levels of sulphate (4.01%) and chloride (4.57%) in sea sand, which jeopardise structural stability. Significant differences between the three types of sand-based blocks were confirmed by statistical analysis using Tukey's HSD test and one-way ANOVA. These results highlight how important strict quality control is when making sandcrete blocks. To improve construction safety and durability, the study suggests giving river and sea sand priority by properly treating them to improve their qualities. This study contributes to the long-term integrity of buildings in Ghana by highlighting the crucial significance of sand selection and offering insightful advice to legislators and construction experts.